A Microvalve Module with High Chemical Inertness and Embedded Flow Heating for Microscale Gas Chromatography - Hsueh-Tsung Lu; Yutao Qin; Yogesh Gianchandani (Sensors, 2021)
This paper reports a multi-valve module with high chemical inertness and embedded flow heating for microscale gas chromatography (µGC) systems. The multi-valve module incorporates a monolithically microfabricated die stack, polyimide valve membranes, and solenoid actuators. The design incorporates three valves within a single module of volume 30.2 cm3, which is suitable for the small form factor of µGC systems. The die stack uses fused silica wafers and polyimide valve membranes that enhance chemical inertness. The monolithic die stack requires only three lithographic masks to pattern fluidic microchannels, valve seats, and thin-film metal heaters and thermistors. The performance of fabricated multi-valve modules is compared to a commercial valve in tests using multiple volatile organic compounds, including alkanes, alcohols, ketones, aromatic hydrocarbons, and phosphonates. The valves show almost no distortion of chromatographic peaks. The experimentally measured ratio of flow conductance is 3.46 × 103, with 4.15 sccm/kPa in the open state and 0.0012 sccm/kPa in the closed state. The response time is <120 ms.